Estimation of stature and body weight from static and dynamic footprints – Forensic implications and validity of non-colouring cream method. (January 2022) - Švábová (nee Uhrová), Petra; Caplova, Zuzana; Beňuš, Radoslav; Chovancová (nee Kondeková), Mária; Masnicová, Soňa
Abstract: In the present study, the metric properties of dynamic footprints were analysed using non-colouring method in relation with body parameters and compared with static footprint measurements. The results of the study provide a better understanding of the relationship between static and dynamic footprints, which may be useful for biological profiling that allows more accurate identification. Stature, body weight, five length and two width parameters of dynamic (walking) footprints of young Slovak adults (65 females and 68 males) were analysed. Pearson correlation coefficients were calculated and equations for prediction of stature and body weight by linear regression analysis and multiple regression analysis were developed. Intersex differences were confirmed for all parameters and bilateral for some. Statistically significant differences were found in all measurements (p-value>0.05), except for the width of the standing and walking footprint in the mixed group. A positive correlation was found between the selected footprint diameters with stature (max - r = 0.82) and body weight (max - r = 0.70). Stature could be calculated with an accuracy of up to 4.40 cm and body weight with an accuracy of up to 9.56 kg. The results of the present study show that selected measurements of dynamic footprints correlate with stature and body weight. These results could be used in biological profiling in the medical and forensic fields. Highlights: Body weight prediction equations from walking footprints were developed. Stature prediction equations from dynamic footprints were calculated. Higher correlations of dynamic footprints parameters with stature were observed. Significant differences between length measurements of standing and walking footprints were confirmed. Non-coloring cream method is reliable to collect footprints.